Regulation of Nutrient Uptake by Plants - Mitra, Gyanendra Nath (Springer, 2015)
This book describes the mechanisms of nutrient taken up by plants at the biochemical and molecular level. This is a new concept developed over the past 30 years, primarily due to use of modern technology developed in biotechnological research, instrumentation, modern computation facilities, bioinformatics, the large volumes of information generated by use of various ‘omics’ and of course the dedicated hard work of a large number of researchers.